EFEKTIVITAS MEDIA GURITA KATA DALAM PEMBELAJARAN MENULIS PUISI BAGI SISWA SEKOLAH DASAR - Setiawan, Heri; Karma, I Nyoman; Hakim, Mansur; Saputra, Heri Hadi; Marijo, M. Okta D. S. F. (SITTAH: Journal of Primary Education, 2023)
Poetry writing material is one of the important contents of learning the Indonesian language and literature in elementary school. However, in its implementation, students needed help understanding the learning material for writing poetry. To overcome this problem, teachers can use learning media. One medium that can be used in teaching poetry writing is the visual octopus word learning media. This media is in the form of an imitation octopus with poetry-writing material on each tentacle. This study was carried out to examine the effectiveness of the word octopus in poetry writing material. This study used a quasi-experimental method with a one-group pretest-posttest design at Public Elementary School (SDN) 1 Kekeri. Preliminary and final test questions regarding poetry writing material were used as the main instruments for data collection. Data collection underwent three stages: an initial test, providing treatment by applying octopus word learning media, and a post-test. Data analysis was carried out in two phases: prerequisites and testing media effectiveness. The study results show that the Octopus Kata learning media has high effectiveness. It can be seen from the significant difference in the average initial and final test results. This study concludes that the octopus word learning medium effectively increases elementary school students' understanding of learning to write poetry.